Effect of fatty acid content on the level of cottonseed colonization by fungi - Aly, Aly; Hussein, Ezzat; Omar, Moawad; El-Abbasi, Ibrahim; Abd-Elsalam, Kamel (Biological Letters, 2012)
Non-sterilized seeds of 12 Egyptain cotton (Gossypium barbadense L.) genotypes were examined for qualitative and quantitative estimates of seed-borne fungi. Rhizopus stolonifer (39.7%), Aspergillus niger (33.5%), and Penicillium sp. (23.3%) were the most predominant fungi isolated from the seeds. Other fungi occurred at frequencies that ranged from 0.3 to 17.7%. Gas-liquid chromatography (GLC) analysis of fatty acid composition of the seeds revealed the presence of the following fatty acids: caproic, caprylic, capric, lauric, myristic, palmitic, margaric, stearic, oleic, linoleic, and linolenic. The total mean percentage of the monounsaturated fatty acids was 59.11%, while that of the unsaturated fatty acids was 16.72%. Isolation frequencies of Alternaria alternata, A. flavus, A. niger were not significantly correlated with the content of any fatty acid. Isolation frequencies of the other fungi were significantly correlated with the content of 1-2 fatty acids. Cladosporium sp. was a notable exception because its isolation frequency was significantly correlated with the content of caproic (r = 0.926, p < 0.01), caprylic (r = 0.638, p < 0.05), palmitic (r = -0.586, p < 0.05), and linoleic acid (r = 0.917, p < 0.01). It was possible to group the isolated fungi into 5 distinct categories based on their sensitivity to the fatty acids (the magnitude of R2 values). The results of the present investigation suggest that certain fatty acids regulate the colonization of cottonseed by fungi, and that the control of these fungi may be possible by modifying the fatty acid content of the seed.